EFFECTIVENESS OF INQURY DISCUSSION ASSISTED IMPLEMENTATION OF POWERPOINT MEDIA IN LIFE ORGANIZATION IN SMP N I PULOKULON - Muhamad Jalil (Universitas Negeri Padang Address: Biology Education Study Program Faculty Mathematics and Natural Science (FMIPA) Jl. Prof. Dr. Hamka Air Tawar Barat, Padang-West Sumatera-Indonesia Telp. +62751-7057420 - Fax.+62751-7058772 - Ph. +6281363229286, 2018)
Biology Learning at SMP N 1 Pulokulon obtained information that the learning process that occurs less involving students. The final test of the first semester for the science subjects was 35.5% of the students got the score ≥ 50, the students' learning completeness for the Biology subject in the school was 65% of students got ≥ 50. The effort to solve the problem was by applying inquiry discussion. This method is combined with PowerPoint media that can display images concretely. This study aims to determine the effectiveness of inquiry discussion assisted application of PowerPoint media in the learning of organizational life on students in SMP N 1 Pulokulon. The type of data consists of: (1) affective and psychomotoric students, obtained by using activity observation sheet and student performance during the learning progress, (2) cognitive students, obtained by multiple choice test given at the beginning and end of learning. Achievement mastery of affective and psychomotor learning result that is ≥ 85% student reach good and very good criterion. Analysis of cognitive data of students using variance analysis, if the F test is significantly different then continued the test of the BNT. The BNT test result in the post test shows that the experimental class is significantly different from the comparison class. Thus it can be concluded that the inquiry discussion with PowerPoint media effectively applied to the material organization of life in students in class VII SMP N 1 Pulokulon.